2018
DOI: 10.1111/ped.13469
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin as a predictor of positive blood culture in suspected neonatal sepsis

Abstract: P-SEP can better discriminate between infections and non-infectious inflammatory conditions than the currently used biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Although many studies have investigated predictors of SBI in young infants by implementing criteria or developing prediction models, [6][7][8] few studies have focused on using the vital signs, such as body temperature, pulse rate, and oxygen saturation. 9 One subgroup analysis of a systematic review showed that young infants with fever >40°C had a significantly high risk of SBI, 13 but no study has defined the cut-off point for each vital sign. The concept of systemic inflammatory response syndrome (SIRS) may be useful in this regard because SIRS is defined according to vital sign cut-offs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although many studies have investigated predictors of SBI in young infants by implementing criteria or developing prediction models, [6][7][8] few studies have focused on using the vital signs, such as body temperature, pulse rate, and oxygen saturation. 9 One subgroup analysis of a systematic review showed that young infants with fever >40°C had a significantly high risk of SBI, 13 but no study has defined the cut-off point for each vital sign. The concept of systemic inflammatory response syndrome (SIRS) may be useful in this regard because SIRS is defined according to vital sign cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to determine whether abnormal vital sign parameters would be able to predict SBI in febrile young infants. An SBI was defined as a clinically diagnosed bacterial infection, such as bacterial meningitis, bacteremia, urinary tract infection (UTI), bacterial pneumonia, bacterial soft‐tissue infection, suppurative lymphadenitis, osteomyelitis, and bacterial enteritis, based on previous studies . Patients with bacterial meningitis, bacteremia, UTI or bacterial enteritis were diagnosed on detection of pathogens from specimens taken from the focus of the infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Um estudo de corte realizado em uma UTI neonatal sugere a existência de outros biomarcadores mais específicos que podem contribuir para o melhor diagnóstico do quadro infecioso. 24 É válido ressaltar que existem vários fatores que podem interferir nos resultados da hemocultura, dentre eles, a coleta que necessita de um local apropriado, volume adequado e momento da execução, além disso, a utilização preferencial de frascos pareados, bem como os procedimentos da fase analítica. Segundo as diretrizes para tratamento de sepse e choque séptico é indispensável realizar as hemoculturas antes de iniciar a antibioticoterapia empírica, devido a probabilidade de resultados falsos-negativos, pelo uso prévio de antibiótico.² As culturas negativas ou não realizadas trazem vários prejuízos ao paciente e ao hospital.…”
Section: Características Epidemiológicas E Clínicas Da Sepse Em Um Hounclassified